A study on the surface deterioration of home made halide sensors - Rajbandari, A; Manandhar, K; Pradhananga, RR (BIBECHANA, 2012)
Home made halide sensors based on silver sulphide-silver halide have been prepared and successfully employed for the determination of iodide, bromide and chlorides ions in solutions. These ion sensors showed a Nernstian response in the concentration range of 10-1 to 10-7 M for iodide ions, 10-6 M for bromide ions, and 10-5 M for chloride ions. The response time of these sensors was < 1 min. We have found that the iodide ion sensor can selectively detect iodide ions in presence of chloride and bromide ions. However, sensing performance of the bromide and chloride sensors are largely interfered by the presence of iodide ions. Surface study showed that surface deterioration of membrane was caused by the solutions containing interfering ions and its regular use, particularly in dilute solutions. DOI: http://dx.doi.org/10.3126/bibechana.v9i0.7143 BIBECHANA 9 (2013) 1-6